Fibroepithelial Polyp of the External Auditory Canal: A Case Report and a Literature Review - Nobuaki Tanaka; Takeshi Matsunobu; Akihiro Shiotani (Case Reports in Otolaryngology)
This paper reports the first case of fibroepithelial polyp arising independently of the external auditory canal. A 16-year-old female patient presented to our clinic for aural fullness of the left side. Physical examination revealed a papillomatous tumor at the posterior wall of the inlet of the left external auditory canal. After biopsy, which yielded a diagnosis of benign papilloma, the patient underwent tumor excision. Final diagnosis was fibroepithelial polyp. One week after resection, aural fullness had resolved. Fibroepithelial polyp is a benign lesion and occurs mainly in the skin, ureteropelvic system, and genitals. In the head and neck area, there are reports on fibroepithelial polyp of the tongue, piriform fossa, inferior nasal turbinate, and tonsil, in addition to the skin, but none on independent fibroepithelial polyp of the external auditory canal. Excision of fibroepithelial polyp of the external auditory canal is advisable, especially in the presence of any symptoms, and should be preceded by confirmation of nonmalignancy by biopsy, if possible.